Pengaruh Keahlian Akuntansi Komite Audit Dan Dewan Komisaris Wanita Terhadap Manajemen Laba - Nita Gusda Putri; Erinos NR (Jurnal Eksplorasi Akuntansi, 2019)
This study aims to determine and analyze the influence of the audit committee’s accounting expertise and the female board of commissioners on earnings management in manufacturing companies listed on the Indonesia Stock Exchange for the period 2015-2017 both simultaneously and partially. Data analysis method used is panel data regression analysis. Using a purposive sampling method to obtain a sample of 63 companies from 121 manufacturing companies. Based on the results of the study it is known that the accounting expertise of the audit committee and female board of commissioners simultaneously influence earnings management. But partially, the audit committee accounting expertise has a positive effect on earnings management and the female board of commissioners has a positive effect on earnings management in manufacturing companies listed on the Indonesia Stock Exchange for the period 2015-2017.